The Influence Of Entrepreneurship Spirit And Entrepreneurship Value On Business Success In Tembung Bersatu Percut Sei Tuan - Retnawati Siregar; Fitriani Tobing; Linda Lores; Dahrul Siregar (Yayasan Cita Cendikiawan Al Kharizmi, 2026)
The purpose of this study was to determine and analyze the influence of entrepreneurial spirit and entrepreneurial values ??on business success in UKM Tembung Bersatu, Percut Sei Tuan District. The research method used is exploratory research, where variables are measured using a Likert scale. Methods of data collection is done by interview (interview), with a list of statements (Questioner) and study documentation. The population in this study were all Tembung Bersatu UKM. totaling 40 SMEs. Sampling using saturated sampling method or better known as a census. In this study, the population was relatively small, namely 40 people. Processing data using SPSS software version 23, with descriptive analysis and hypothesis testing multiple regression analysis. The results showed that partially or simultaneously the variables of entrepreneurial spirit and entrepreneurial value had a positive and significant effect on business success in Tembung Bersatu SMEs, Percut Sei Tuan sub-district